2014
DOI: 10.1016/j.micres.2013.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol of Rhizoctonia solani damping-off and promotion of tomato plant growth by endophytic actinomycetes isolated from native plants of Algerian Sahara

Abstract: Thirty-four endophytic actinomycetes were isolated from the roots of native plants of the Algerian Sahara. Morphological and chemical studies showed that twenty-nine isolates belonged to the Streptomyces genus and five were non-Streptomyces. All isolates were screened for their in vitro antifungal activity against Rhizoctonia solani. The six that had the greatest pathogen inhibitory capacities were subsequently tested for their in vivo biocontrol potential on R. solani damping-off in sterilized and non-sterili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
76
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(99 citation statements)
references
References 41 publications
14
76
0
2
Order By: Relevance
“…However, since the production of antibiotics is strain-specific (Hotta & Okami, 1996), we cannot conclude if the antimicrobial activity of our S. niveus and S. humidus isolates was based on the aforementioned antibiotics. We isolated actinobacteria belonging to species that have shown antifungal activity: endophytic M. aurantiaca and rhizospheric S. luteoverticillatus include antifungal strains, and S. cyaneofuscatus has shown both in vivo and in vitro activity (Goudjal et al, 2014;Kim et al, 2012a;Zhao et al, 2012). The different antimicrobial ranges of the S. luteoverticillatus isolates from the rhizosphere of Stellera chamaejasme L. and from G. inflate was in accordance with the strain-specificity of antimicrobial activity.…”
Section: Discussionmentioning
confidence: 77%
“…However, since the production of antibiotics is strain-specific (Hotta & Okami, 1996), we cannot conclude if the antimicrobial activity of our S. niveus and S. humidus isolates was based on the aforementioned antibiotics. We isolated actinobacteria belonging to species that have shown antifungal activity: endophytic M. aurantiaca and rhizospheric S. luteoverticillatus include antifungal strains, and S. cyaneofuscatus has shown both in vivo and in vitro activity (Goudjal et al, 2014;Kim et al, 2012a;Zhao et al, 2012). The different antimicrobial ranges of the S. luteoverticillatus isolates from the rhizosphere of Stellera chamaejasme L. and from G. inflate was in accordance with the strain-specificity of antimicrobial activity.…”
Section: Discussionmentioning
confidence: 77%
“…2). The 16S-rRNA based sequences of the identified actinomycetes indicated that these strains have high identity with known beneficial microbes that have several potential traits, such IAA production, growth promoter, and biocontrol activity, which can be utilized for agriculture crop yield [9,30,31]. Fig.…”
Section: Morphological and Molecular Identification Of Actinomycetesmentioning
confidence: 99%
“…Ezziyyani et al (2007) purified, from S. rochei, the compound 1 propane, 1-4 chlorophenyl with antagonistic capacity against this phytopathogen. There are very few studies on the application of actinomycetes in the biocontrol of diseases under plant conditions; however, recently, Goudjal et al (2014) found that application of a consortium of six actinomycetes coated in tomato seeds reduced, by up to 86.6%, the of incidence on the disease known as damping-off caused by Rhizoctonia solani in seedbeds with infested substrate. Additionally, this application significantly increased biomass, root length, and seedlings.…”
Section: Plant Growth Promotion By Amf and Actinomycetesmentioning
confidence: 99%